Improved evidence-base for Rwanda's National Strategy for Transformation and Vision 2050 - CGIAR Research Program on Policies, Institutions, and Markets (2019)
To support Rwanda’s Ministry of Planning and Finance, the World Bank commissioned IFPRI I to carry out an analysis to evaluate alternative growth paths and investment priorities for agriculture and urban development. This request drew on earlier PIM-supported models, data and research on urban-rural linkages and the effects of urbanization of agricultural transformation. The results of the analysis informed Rwanda’s National Strategy for Transformation and Vision 2050 policy documents.